Developmental Topographical Disorientation With Concurrent Face Recognition Deficit: A Case Report - Rusconi, Maria Luisa; Fusi, Giulia; Stampatori, Chiara; Suardi, Angelo; Pinardi, Chiara; Ambrosi, Claudia; Costa, Tommaso; Mattioli, Flavia (Frontiers in Psychiatry, 2021)
Developmental topographical disorientation (DTD) has been defined as a developmental deficit in human navigational skills in the absence of congenital or acquired brain damage. We report the case of LISA (Lost In Space Again), a 22-year-old woman with a normal development and no clinical history of neurological or psychiatric diseases, evaluated twice, with an interval of 5 years. The Magnetic Resonance Imaging (MRI) examination did not reveal any morphological alteration while Diffusion Tensor Imaging (DTI) showed a structural connectivity deficit (a decreased fractional anisotropy-FA) in the parieto–prefrontal and parieto–premotor pathway. The behavioral assessment showed different deficits in spatial and navigational tasks which seemed to be connected to a poor ability to form a cognitive map of the environment. Moreover, LISA displayed a poor performance in high level face encoding and retrieval. The aim of this case report is to share new insight about DTD in order to deepen the knowledge of this specific neurodevelopmental disorder. In conclusion, this novel DTD case: 1) supports the hypothesis of the existence of different DTD’s subtypes; 2) sustains the evidence that DTD can co-occur (or not) with deficit in face recognition; 3) highlights the need for an in-depth examination from both a neurocognitive and behavioral point of view of a possible common developmental defect between the formation of cognitive maps and the recognition of faces that might be in mental imagery skills. Future directions will be also discussed.